ANALISIS PENGELOLAAN DAN UPAYA PENYELESAIAN KREDIT MACET PADA PT. BPR LPN SUNGAI RUMBAI PERIODE TAHUN 2024 - Hidayatullah, Chindy; Ermawati , Eka; Wiska, Mayroza (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
Based on research aimed at analyzing the management and resolution of non-performing loans at PT. BPR LPN Sungai Rumbai during 2024, it can be concluded that non-performing loans are indeed a serious challenge because they can disrupt the bank's financial stability and reduce customer confidence. Using qualitative descriptive methods and a case study approach, data was collected through observation, interviews, and documentation. The results of the study show that the non-performing loan rate reached 10%, double the OJK maximum limit of 5%. To deal with this, BPR implemented various strategies such as creditworthiness evaluation, active collection, credit restructuring, and collateral seizure, which were applied in about 50% of cases. The main factor causing non-performing loans was the debtor's inability to meet their obligations due to a decline in income. In conclusion, the credit restructuring policy is the most effective solution because it adjusts to the debtor's financial condition. The findings of this study have been validated through data triangulation, ensuring the reliability and accuracy of the results. In addition, the implementation of adaptive restructuring oriented towards the debtor's economic recovery has proven to be able to significantly reduce the risk of non-performing loans in the long term.